Approaching Subjectivity. On “The Dispute About Subjectivity: Interdisciplinary Perspective” - Napiwodzka, Karolina (ETHICS IN PROGRESS, 2018)
The review paper revisits the problem of subjectivity with particular focus on the latest research in this field presented in The Dispute about Subjectivity – an Interdisciplinary Perspective, edited by Adriana Warmbier (2016). I pay special attention to the interdisciplinary perspective of the analyzed issues of subjectivity as a research object in humanities (philosophy, psychology, anthropology) and cognitive sciences.